The Great Resignation and the War for Talent: Understanding Employee Turnover in the Post-Pandemic Era - Estiana, Ria; Mulyani, Yani Sri; Akhmad, Jaenudin (Journal of Economics and Management Scienties, 2025)
The COVID-19 pandemic triggered a global redefinition of work, catalyzing a historic wave of voluntary resignations known as The Great Resignation and intensifying the competition for skilled labor—often referred to as the War for Talent. This study presents a systematic literature review of 38 peer-reviewed articles published between 2019 and 2024 to investigate the multidimensional drivers of employee turnover and evaluate organizational responses in the post-pandemic context. The findings reveal four key thematic areas: psychological and value-driven resignation behavior, evolving work models and employee expectations, strategic talent retention efforts, and sectoral or regional variations in turnover patterns. The analysis also identifies a shift toward human-centered, data-informed HRM strategies and the growing influence of AI and digital infrastructure in workforce management. Furthermore, the study discusses emerging theoretical frameworks, such as Adaptive HRM and Human-Centered Design, offering fresh perspectives on employee engagement and retention. The review concludes that employee turnover in the post-pandemic era reflects enduring structural transformations rather than temporary labor market anomalies, necessitating holistic, empathetic, and context-sensitive strategies by both organizations and policymakers.